2006
DOI: 10.1073/pnas.0603494103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen chloride-induced surface disordering on ice

Abstract: Characterizing the interaction of hydrogen chloride (HCl) with polar stratospheric cloud ice particles is essential for understanding the processes responsible for ozone depletion. We studied the interaction of gas-phase HCl with ice between 243 and 186 K by using (i) ellipsometry to monitor the ice surface and (ii) coated-wall flow tube experiments, both with chemical ionization mass spectrometry detection of the gas phase. We show that trace amounts of HCl induce formation of a disordered region, or quasi-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
182
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(204 citation statements)
references
References 42 publications
20
182
2
Order By: Relevance
“…The observation of reversible adsorption is in agreement with other data available for weak acids or non-acidic species such as H 2 O 2 (Pouvesle et al, 2010), acetone (Winkler et al, 2002;Peybernes et al, 2004;BartelsRausch et al, 2005), formic acid (von Hessberg et al, 2008) and acetic acid (Sokolov and Abbatt, 2002;Symington et al, 2010). For the strong acids HNO 3 and HCl (McNeill et al, 2006) the peak area was significantly lower in the desorption experiments, showing that the adsorption was not reversible for these strong acids. In summary, the uptake of HO 2 NO 2 to the ice surface can be described as reversible adsorption equilibrium at temperatures from 230 K to 253 K.…”
Section: Adsorption Experimentssupporting
confidence: 91%
See 2 more Smart Citations
“…The observation of reversible adsorption is in agreement with other data available for weak acids or non-acidic species such as H 2 O 2 (Pouvesle et al, 2010), acetone (Winkler et al, 2002;Peybernes et al, 2004;BartelsRausch et al, 2005), formic acid (von Hessberg et al, 2008) and acetic acid (Sokolov and Abbatt, 2002;Symington et al, 2010). For the strong acids HNO 3 and HCl (McNeill et al, 2006) the peak area was significantly lower in the desorption experiments, showing that the adsorption was not reversible for these strong acids. In summary, the uptake of HO 2 NO 2 to the ice surface can be described as reversible adsorption equilibrium at temperatures from 230 K to 253 K.…”
Section: Adsorption Experimentssupporting
confidence: 91%
“…Yet, surface modification of the ice by HNO 3 could be important along the first 2 cm of the CWFT. McNeill et al (2006) have observed increased adsorption of acetic acid to ice when another strong acid, HCl, was dosed to the surface at a concentration that induced surface premelting. McNeill et al (2006) observed this increased adsorption at HCl concentrations near the boundary of the solid ice stability regime of the HCl-water phase diagram.…”
Section: Effect Of By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable results have also been obtained with many other oxygenated VOC species, such as acetaldehyde (Petitjean et al, 2009), formic and acetic acids (Jedlovszky et al, 2008;Symington et al, 2010), and alcohols (Kerbrat et al, 2007;Abbatt et al, 2008). A few studies have also shown that the coadsorption of a VOC with another trace gas onto the ice surface can be described well using a competitive Langmuir adsorption model Kerbrat et al, 2010) in the absence of chemically-induced surface changes (McNeill et al, 2006).…”
Section: Molecular-level Picturementioning
confidence: 82%
“…simultaneous condensation of trace gases and water vapour on the ice surface), and dissolution into the quasi-liquid layer (QLL). The impact of QLL should increase by raising the temperature [60]. Abbatt et al [61] measured an enhanced uptake for benzene and acetone at high temperature.…”
Section: Nomentioning
confidence: 99%